2015
DOI: 10.1007/978-3-319-20591-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Firm-Dynamics on Japanese Interfirm Trade Network

Abstract: We analyze Japanese interfirm trade network data for 20 years from the viewpoint of the metabolism of scale-free network evolution. We find that the preferential attachment effect of established firms is stronger than that of merged firms. This shows that merging firms should choose counterparties using delicate business strategies that may not be related to the degree. We also find that the distribution of lifespan of links is approximated well by an exponential function with the characteristic time of 6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Business and trade networks provide well-studied economic examples of directed networks that allow for detailed investigations of the aforementioned questions. In business networks, individual firms are interpreted as nodes [12]. If a business or trade relationship between two firms is reported, a link between the involved nodes is drawn.…”
Section: J Stat Mech (2017) 053404mentioning
confidence: 99%
See 1 more Smart Citation
“…Business and trade networks provide well-studied economic examples of directed networks that allow for detailed investigations of the aforementioned questions. In business networks, individual firms are interpreted as nodes [12]. If a business or trade relationship between two firms is reported, a link between the involved nodes is drawn.…”
Section: J Stat Mech (2017) 053404mentioning
confidence: 99%
“…Equation (7) accounts for the assumption that more common business relations make a reconnection to node l more likely. Models G • that include the relinking process are denoted with the additional subscript l. https://doi.org/10.1088/1742-5468/aa6ddb approximately reproduces the scale-free degree distribution from the real-world network, following a power law ∝ k −α with an exponent of α ≈ 1.4 [12]. Despite changes in the number of firms and links, it has been concluded that some basic characteristics such as the degree distribution are robust in the business firm network of Japan from 1994 to 2014 [12].…”
Section: Substitution Of Trading Partnersmentioning
confidence: 99%
“…Nevertheless, different scaling exponents might also be relevant to differences in actual dynamics of companies. For example, the number of companies having 5-10 trading partners are more than expected from the powerlaw tail of the distribution in our dataset (as seen in [54]). This might suggest that there is a 'barrier' that prevents those in the small-company regime from entering the large-company regime.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, although not covered in this paper, the analysis of such network structures as inter-firm transactions and corporate shareholding has increased the understanding of the microstructures of corporate connections (See Refs. Goto et al [13]; Mizuno et al [14]).…”
Section: Introductionmentioning
confidence: 99%